Pemanfaatan Tandan Pisang Kepok sebagai Sumber Alkali pada Pembuatan Sabun Cair - Amelia, Reny Elvira; Hasibuan, Rosdanelli; Irvan (Talenta Publisher (Universitas Sumatera Utara), 2023)
Kepok banana bunches were used as a source of natural alkali in the study of determining the ratio of coconut oil and palm oil in the saponification process using banana bunch ash. Alkali is obtained from the calcination process with variations in temperature of 400 °C, 500 °C, 600 °C, and 700 °C for 4 hours. Characterization of potassium from Kepok banana bunch ash using Atomic Absorption Spectrophotometer resulted in the highest potassium being 58.41% at 600 °C. The potassium obtained is used as a source of alkali in the saponification process of liquid bath soap. In this study, variations in the amount of alkali (30%, 40%, 50%, and 60%), the ratio of coconut oil and palm oil (60:40, 70:30, 80:20, and 90:10 (w/w)) with reaction times were carried out 2.5 hours, 3 hours, and 3.5 hours. The best liquid bath soap was obtained at a ratio of 70:30 (w/w) coconut oil and palm oil and 30% alkali with a reaction time of 2.5 hours which was 81.34%.